A FEN 1-driven DNA walker-like reaction coupling with magnetic bead-based separation for specific SNP detection - Xu, Shijie; Chen, Jian; Yang, Fang; Yang, Zhihao; Xu, Jianrong; Wang, Lanyue; Bian, Lina; Liu, Lihua; Zhao, Xiaoyu; Zhang, Yunshan (Frontiers in Bioengineering and Biotechnology, 2023)
Single-nucleotide polymorphism (SNP) plays a key role in the carcinogenesis of human genome and understanding the intrinsic relationship between individual genetic variations and carcinogenesis lies heavily in establishing a precise and sensitive SNP detection platform. Given that, a powerful and reliable SNP detection platform is proposed by flap endonuclease 1 (FEN 1)-driven DNA walker-like reaction coupling with magnetic bead (MB)-based separation. Carboxyfluorescein (FAM) labeled downstream probe (DP) was decorated on streptavidin magnetic bead (SMB). The target DNA, as a walker strand, was captured by hybridizing with DP and upstream probe (UP) to form three-base overlapping structure and execute walking function on the surface of SMB. FEN 1 was employed to specifically recognize the three-base overlapping structure and cut the 5' flap at SNP site to report the walking event and signal amplification. Considering the fact that fluorescence was labeled on cleavage and uncleavage sequence of DP and the target DNA triggered walking event was undistinguished from the mixtures, magnetic separation came in handy for cleavage probe (CP) isolation and discriminating the amplified signal from background signal. In comparison with conventional DNA walker reaction, this strategy was coupled with SMB-based separation, thus promising a powerful and reliable route for SNP recognition and signal amplification.